Pengaruh Penyimpanan Beku Minced Fish Dan Frekuensi Pencucian Terhadap Kualitas Mutu Surimi Dan Kamaboko Ikan Patin (Pangasius sp.) - Gressty Sari Br Sitepu; Gevbry Ranti Ramadhani Simamora (Universitas Negeri Gorontalo, 2022)
The study aimed to analyze the effect of frozen minced fish storage and washing cycle to the quality of surimi and kamaboko catfish (Pangasius sp). The experimental design used was randomized compact design with treatment of storage time (0,14,28) day and washing cycle treatment (1,2,3, and 4). The results showed that the storage time and washing frequency significantly affect the expressible water, while not significant effect on white duct, folding test and teeth cutting test. The highest values of surimi and kamaboko catfish from each treatment are whiteness test at surimi of 49,27% and 63.55% at kamaboko, folding test with value 7, teeth cutting test 7 and expressible water have the highest value of 35 at kamaboko and has a TVBN value which is still below the decay threshold, which is in the range of 11.295-12.085 mg N/100 g.